Use of Integrated Mobile Application With Realistic Mathematics Education: A Study to Develop Elementary Students’ Creative Thinking Ability - Rudyanto, Hendra Erik; Ghufron, Anik; Hartono, Hartono (International Journal of Interactive Mobile Technologies (iJIM), 2019)
One of the abilities students must possess is Creative Thinking Ability (CTA) in order to succeed in their lives. Learning must facilitate students to develop CTA; one of them is by developing a mobile application based on Realistic Mathematics Education (RME). The purpose of this study is to determine the level of validity/feasibility, practicality, and effectiveness of mobile application based RME. This mobile application development used the ADDIE model development procedure. The subjects in this study were grade 4 elementary school students. The validation data collection techniques through validation sheets, practicality data through CTA tests. The results of the study show that the developed of mobile application integrated with realistic mathematics meets valid/proper requirements based on expert and practitioner assessments that are practical and easy if applied in mathematics learning and that is effective in improving students’ creative thinking ability.